Analisis Current Ratio dan Cash Ratio terhadap Kinerja Keuangan Pada PT Wijaya Karya (Persero) Tbk Periode Tahun 2008 - 2017 - Mira Ismirani Fudsyi; Kurniawan Agil (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
This study aims to determine and analyze the significant influence of the current ratio partially on financial performance at PT Wijaya Karya (Persero) Tbk. Period of 2008-2017. To find out and analyze the significant effect of cash ratio partially on financial performance at PT Wijaya Karya (Persero) Tbk. Period of 2008-2017. To find out and analyze the significant effect of simultaneous current ratio and cash ratio on financial performance at PT Wijaya Karya (Persero) Tbk. Period of 2008-2017. The research method used in this research is Descriptive Statistics Analysis with a quantitative approach. Data collection techniques using the study of literature and documentation. Data analysis using Multiple Regression Linear Analysis, Determination Coefficient Analysis and Hypothesis Testing through t test for partial and F test for simultaneous. The results of the study that simultaneously the current ratio and cash ratio do not significantly influence the financial performance of PT. Wijaya Karya (Persero) Tbk. Period of 2008-2017. Partially the current ratio does not have a positive and significant effect on financial performance at PT. Wijaya Karya (Persero) Tbk. Period of 2008-2017. Partially the cash ratio does not have a positive and significant effect on financial performance at PT. Wijaya Karya (Persero) Tbk. Period of 2008-2017.